A comparison of oncological outcomes after abdominoperineal excision before and after the implementation of a selective perineal flap closure program. Issue 2 (25th November 2020) - Murphy, Claudine; Stephens, Ian; OꞌFlanagan, Grace; OꞌByrne, Lisa; Reynolds, Ian S.; Ajmal, Nadeem; O'Sullivan, John Barry; OꞌNeill, Brian; Deasy, Joseph; Burke, John P.; McNamara, Deborah A.
Abstract: Background and Objectives: Abdominoperineal excision (APE) is the operation chosen when a patient has low rectal cancer unamenable to sphincter preserving surgery. Perineal flap reconstruction is associated with less wound morbidity but little is known about oncological outcomes. The objective was to compare outcomes in patients undergoing APE before and after the introduction of a program that utilized flap reconstruction of the perineum. Methods: A retrospective review of a prospectively maintained database was performed. Patients who underwent APE followed by primary closure or flap reconstruction between 1998 and 2018 were selected. The cohorts were divided according to the implementation of the flap reconstruction program in July 2009. Clinicopathological data, recurrence and survival were compared between the cohorts. Results: One hundred and forty nine patients underwent APE for rectal adenocarcinoma between 1998 and 2018. There were 57 patients in the pre‐flap era and 92 in the post‐flap era. Forty‐six patients underwent flap reconstruction in the latter cohort (50%). More patients in the post‐flap era underwent neoadjuvant chemoradiotherapy (85.9% vs. 63.2%; p < .01). Margin positivity rates decreased from 21.1% in the pre‐flap era to 10.9% in the post‐flap era ( p = .10) and there was an associated improvement in incidence and time to local recurrence ( p = .03). Conclusion: The use of perineal flap reconstruction is associated with a longer median time to local recurrence. Perineal flap reconstruction may contribute to reduced margin positivity.